Formation of Rutile Titania Phase at Low Temperature. (2015) - Islam, Shumaila; Rahman, Rosly Abdul; Riaz, Saira; Naseem, Shahzad; Ottoman, Zulkafli
Abstract: The aim of this study is to synthesize and observe the most stable rutile titania phase at low temperature using spin coated sol-gel method. The deposited film was studied on a copper substrate. The XRD traces shows complete phase transformation of metastable anatase and brookite phases into the most stable rutile phase after 2 h heating at 300 °C temperature. FTIR analysis confirmed the homogeneous bonding of titania at low temperature.